2020
DOI: 10.3390/cells9020342
|View full text |Cite
|
Sign up to set email alerts
|

Loading of Primary Human T Lymphocytes with Citrate-Coated Superparamagnetic Iron Oxide Nanoparticles Does Not Impair Their Activation after Polyclonal Stimulation

Abstract: For the conversion of immunologically cold tumors, characterized by a low T cell infiltration, into hot tumors, it is necessary to enrich T cells in the tumor area. One possibility is the use of magnetic fields to direct T cells into the tumor. For this purpose, primary T cells that were freshly isolated from human whole blood were loaded with citrate-coated superparamagnetic iron oxide nanoparticles (SPIONCitrate). Cell toxicity and particle uptake were investigated by flow cytometry and atomic emission spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 65 publications
(82 reference statements)
1
24
0
Order By: Relevance
“…Although effective for lymphoid cell loading, MNP functionalization complicates synthesis and cell handling which would introduce increased variability in MNP-lymphoid cell preparation. Indeed, we and others have described that lymphoid cell loading with minimally functionalized MNPs could be sufficient to achieve magnetic retention [78,79,81]. Our microscopy analysis and iron uptake measurements showed that positively charged MNPs (3-aminopropyl-triethoxysilane (APS)-MNPs) were most associated with all types of lymphoid cells [78].…”
Section: The Interaction Between Mnps and Lymphoid Cellsmentioning
confidence: 65%
See 4 more Smart Citations
“…Although effective for lymphoid cell loading, MNP functionalization complicates synthesis and cell handling which would introduce increased variability in MNP-lymphoid cell preparation. Indeed, we and others have described that lymphoid cell loading with minimally functionalized MNPs could be sufficient to achieve magnetic retention [78,79,81]. Our microscopy analysis and iron uptake measurements showed that positively charged MNPs (3-aminopropyl-triethoxysilane (APS)-MNPs) were most associated with all types of lymphoid cells [78].…”
Section: The Interaction Between Mnps and Lymphoid Cellsmentioning
confidence: 65%
“…Since these cells are barely metabolically active and present a low number of mitochondria in the early stages, these data indicate that MNPs could promote some metabolic activity in resting lymphoid cells. In line with this observation, Mühlberger et al observed a slight decrease in the percentage of naïve T cells after MNP treatment, both in resting cells and in polyclonally-stimulated cells, hinting that MNP loading may facilitate T cell activation [81]. It has been recently reported that activation of pattern recognition receptors (PRR), which include Toll-like receptor (TLRs) and play a role in the initiation of innate immune responses, can regulate TCR signals and T cell functions [107].…”
Section: The Interaction Between Mnps and Lymphoid Cellsmentioning
confidence: 67%
See 3 more Smart Citations